2019
DOI: 10.37077/25200860.2019.125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IGF-1 and GH Genes Polymorphism on Weights and Body Measurements of Awassi Lambs in Different Ages

Abstract: The study was carried on 68 ewes of local Awassi sheep in the Al-Kafeel sheep station Karbala governorate, Iraq for the period from 1/10/2017 to 1/8/2018. Genetic analysis was carried out in the molecular genetics laboratory at the College of Agriculture / Basrah University in order to extract (DNA) and determine the genotype  of the IGF-1(Insulin-like growth factor 1) and GH (Growth Hormone) genes. This study aimed to know the association between the genotype of the ewes of IGF-1 and GH  genes and their relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The statistical analysis results showed the effect of IGF-1 gene genotype was insignificant on body weight and size. These results are in line with the results reported by Al Qasimi et al (2019), studying the effect of IGF-1 and GH genes on body weight and size in Awassi sheep. Gholibeikifard et al (2013) discovered no relationship between exon 3 IGF-1 polymorphism and birth, weaning, six-month, nine-month, and once-a-year weights for the Baluchi sheep.…”
Section: Relationship Of Genotype With Body Sizesupporting
confidence: 93%
“…The statistical analysis results showed the effect of IGF-1 gene genotype was insignificant on body weight and size. These results are in line with the results reported by Al Qasimi et al (2019), studying the effect of IGF-1 and GH genes on body weight and size in Awassi sheep. Gholibeikifard et al (2013) discovered no relationship between exon 3 IGF-1 polymorphism and birth, weaning, six-month, nine-month, and once-a-year weights for the Baluchi sheep.…”
Section: Relationship Of Genotype With Body Sizesupporting
confidence: 93%
“…The SNPs G871A, G1383A, and A1509G affected Harri sheep's LW [42]. Awassi ewes' GH gene variant affects lamb BW as well as the WH, RH, and CC between birth and weaning [43]. Furthermore, an SNP on the GH gene intron 2 region (C>A) significantly affects the LW of Santa Ines sheep on the 100th day [44].…”
Section: Discussionmentioning
confidence: 99%
“…Naicy et al (2017) reported a significant association of the IGF-1 genotype with BH and chest circumference in Attappady Black goats of Kerala. Al Qasimi et al (2019) found a significant (P < 0.05) effect of IGF-1 genotypes on BH, HG and PG. Zhang et al (2008) investigated the polymorphism of the IGF-I gene and its association with growth and body size traits in Nanjiang Huang goats.…”
Section: Effect Of Polymorphism On Performance and Body Conformation ...mentioning
confidence: 88%
“…Negahdary et al (2013) reported a significant association of the IGF-1 genotype with B-WT, W-WT and 6M-WT in Makooei sheep. Al Qasimi et al (2019) found a significant (P < 0.05) effect of IGF-1 genotypes on weights of lambs at weaning and at 6 months of age with the superior genotype GC and non-significant effects on birth weight. Hajihosseinlo et al (2013) observed the significant effects of nucleotide variation in the 5 0 flanking region of the IGF-I gene with several growth traits in Makooei sheep: birth weight (BWT), weaning weight (W-WT), 6-month weight (6M-WT) and average daily gains from birth to weaning (GBW).…”
Section: Effect Of Polymorphism On Performance and Body Conformation ...mentioning
confidence: 93%